1988
DOI: 10.1097/00005053-198809000-00009
|View full text |Cite
|
Sign up to set email alerts
|

High Potency Neuroleptics and Violence in Schizophrenics

Abstract: In a conti'olled stucly, inpatient violence was measured cluring placebo, high-potency (halopericlol) and lorv-potency (chlorpromazine or clozapine) neuroleptics. Some patients had a markecl increase in violent behavior rvith the mocleratelv high-dose haloperidol, but not u,ith lou,-potency neuroleptics. The authors cliscuss reasons for the inct'easecl vioience rvith halopericlol, inclucling al Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Although there is no Emergency Medicine study to document this finding, Herrera et al found this situation on a psychiatric floor (37). They studied 16 male schizophrenic patients resistant to previous neuroleptic treatment.…”
Section: Treatment Of the Agitated Patientmentioning
confidence: 97%
See 1 more Smart Citation
“…Although there is no Emergency Medicine study to document this finding, Herrera et al found this situation on a psychiatric floor (37). They studied 16 male schizophrenic patients resistant to previous neuroleptic treatment.…”
Section: Treatment Of the Agitated Patientmentioning
confidence: 97%
“…It was uncertain whether this effect could be from akathisia or drug-induced behavioral toxicity. This idiosyncratic medication effect should be considered when additional doses of antipsychotics seem to make the agitation worse (37).…”
Section: Treatment Of the Agitated Patientmentioning
confidence: 99%
“…The subjective component consists of a feeling of inner tension and restlessness that, on occasion, can be so distressing that it leads to violent behavior and suicide. 42,43 The objective component takes the form of stereotypic movements, such as shifting from one position to another, rocking, and repetitive touching (e.g. self-caressing mannerisms), 30 and in this regard can resemble restless legs syndrome, 44 but usually without the characteristic paresthesias of the latter.…”
Section: Parkinsonismmentioning
confidence: 99%
“…There were 96 with transient hypotension, 40 with dystonia, three with seizures, two with respiratory arrests, and one with a cardiac arrest (level II) (72). It is interesting to note that one small study demonstrated a marked increase in violent behavior with high potency (haloperidol) vs. low potency neuroleptics (chlorpromazine) (level II) (74). Although many side effects of the anti-psychotics are problematic, problems with droperidol have resulted in FDA "black box" labeling.…”
Section: Chemical Restraintsmentioning
confidence: 99%